SPE Annual Technical Conference and Exhibition 2002
DOI: 10.2118/77675-ms
|View full text |Cite
|
Sign up to set email alerts
|

Proving It – A Review of 80 Published Field Studies Demonstrating the Importance of Increased Fracture Conductivity

Abstract: Many engineers disregard laboratory reports demonstrating that the pressure losses across proppant samples are substantial. Similarly, it appears that the modeling studies warning of substantial productivity losses due to inadequate fracture conductivity have not been universally convincing. Perhaps many practical frac engineers simply object to the theoretical nature of these arguments, when they quote one of the more influential orators of our time, Shania Twain,1 stating, "That don't impre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(20 citation statements)
references
References 122 publications
0
20
0
Order By: Relevance
“…al. 1998;Wahl 1965;Vincent 2002) confirmed that hydraulic fractures provide a much larger surface to allow better communication from the formation to the wellbore.…”
Section: Introductionmentioning
confidence: 86%
“…al. 1998;Wahl 1965;Vincent 2002) confirmed that hydraulic fractures provide a much larger surface to allow better communication from the formation to the wellbore.…”
Section: Introductionmentioning
confidence: 86%
“…However, the fractures tend to close after a hydraulic fracturing operation and thus suitable proppants have to be selected, blend in a certain ratio with the fracturing fluid, fill the fractures, and keep them open after fluid injection [2]. Therefore estimation of the residual openings [46,104,105] or the permeability of the fracture openings [106], which are filled with proppants, as well as the optimisation of the used proppants [107] is of great significance for EGR/EOR applications. A number of studies have focused on the transport of suspended proppant particles within the fracture and the interaction between the formation and the proppant.…”
Section: Developments On Modelling Of Hydraulic Fracturing and Enginementioning
confidence: 99%
“…Although intuition often suggests that any fracture will provide infinite flow capacity compared to the formation, the immense surface area of propped fractures requires fluid to move hundreds of thousands, or even millions of times faster within the propped fractures than within the matrix (33) . Therefore, conductivity of proppant packs remains critical, both for cleanup of frac fluid and subsequent gas production (34,35) . More research and direct observations of proppant transport phenomena will hopefully shed more light on this important topic in the future.…”
Section: Conductivity and Proppant Transport In Light Sand Fracture Tmentioning
confidence: 99%